2016
DOI: 10.1186/s13063-016-1240-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness, quality of life and cost-effectiveness of Flaminal® versus Flamazine® in the treatment of partial thickness burns: study protocol for a randomized controlled trial

Abstract: BackgroundPartial thickness burns are painful, difficult to manage and can have a negative effect on quality of life through scarring, permanent disfigurement and loss of function. The aim of burn treatment in partial thickness burns is to save lives, stimulate wound healing by creating an optimumly moist wound environment, to have debriding and analgesic effects, protect the wound from infection and be convenient for the patient and caregivers. However, there is no consensus on the optimal treatment of partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
(50 reference statements)
0
11
0
Order By: Relevance
“…Patients with partial thickness burns participated in an open label, multicenter RCT comparing the clinical effectiveness, quality of life, and costs of enzyme alginogel with SSD. The detailed study protocol was published previously . The study was approved by the Medical Research Ethics Committee Noord‐Holland (NL43671.094.13) and conducted at two Dutch Burn Centers (Red Cross Hospital, Beverwijk and Maasstad Hospital, Rotterdam) from February 2014 until September 2015.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with partial thickness burns participated in an open label, multicenter RCT comparing the clinical effectiveness, quality of life, and costs of enzyme alginogel with SSD. The detailed study protocol was published previously . The study was approved by the Medical Research Ethics Committee Noord‐Holland (NL43671.094.13) and conducted at two Dutch Burn Centers (Red Cross Hospital, Beverwijk and Maasstad Hospital, Rotterdam) from February 2014 until September 2015.…”
Section: Methodsmentioning
confidence: 99%
“…Two retrospective studies showed faster wound healing when enzyme alginogel, which is a hydrated alginates polymers in a polyethyleneglycol (PEG) matrix embedded with a biologic enzyme system of glucose oxidase, lactoperoxidase and guaiacol was compared with SSD in the treatment of partial thickness burns, while no data were available with regard to scar formation, HRQoL, costs, or cost‐effectiveness . Therefore, our research group performed a randomized controlled trial (RCT) comparing enzyme alginogel with SSD in the treatment of partial thickness burns (FLAM study) . Enzyme alginogel was not found to be superior with regard to clinical outcomes such as wound healing time (primary outcome), pain, incidence of infection, and scar quality, although patients in the enzyme alginogel group required significantly less dressing changes compared with the SSD group .…”
Section: Introductionmentioning
confidence: 99%
“…In this investigator‐initiated, open label, multicenter, randomized controlled trial (RCT) we compared the clinical effectiveness of Flaminal® Forte versus Flamazine® in the treatment of partial thickness burns. An extensive description of the study protocol was published previously . The results are reported following the Consolidated Standards of Reporting Trials (CONSORT) guidelines .…”
Section: Methodsmentioning
confidence: 99%
“…The following baseline parameters were collected for both study arms: age, gender, wound etiology, bacterial contamination at admission, location and type of the wound, TBSA and co‐morbidities. The burn depth of the study area was accurately determined on day 2–5 post burn by clinical assessment and Laser Doppler Imaging (LDI), using a MoorLDI2‐Burn Imager™ (Moor Instruments, UK) and based on predefined criteria . Studies demonstrated that LDI has an accuracy of 95% in combination with clinical estimation, for assessing burn wound depth …”
Section: Methodsmentioning
confidence: 99%
“…2 Burn treatment aims to promote complete and rapid healing of wounds, reduce pain, protect the wound, prevent infection, and reduce physical sequelae and functional disability. 3 For decades, routine management has centered on ointments and dressings containing 1% silver sulfadiazine (SSD) as the gold standard treatment for burns, due to the drug's antimicrobial properties against a wide range of gram-positive and gram-negative microorganisms. 3 However, like all drugs, SSD has some undesirable effects, such as decrease in wound contraction, black scars, delayed development of granulation tissue, limited depth of penetration in lesions, risk of silver toxicity, and neutropenia.…”
Section: Introductionmentioning
confidence: 99%